Halal tourism: Emerging opportunities - Mohsin, Asad; Ramli, Noriah; Alkhulayfi, Bader Abdulaziz (Elsevier USA, 2016)
The main purpose of this paper is to raise awareness about the growing Halal tourism market segment and identify the fundamental needs of this segment. What is Halal tourism? What are the sources that inform about Halal tourism? What is the potential of Halal tourism? How does one attract this potential segment? These are some of the questions to which a response is provided in the paper. The methodology is largely reliant on secondary information. The paper also makes some recommendations which have implications for the practitioners.